Effect of structural economic vulnerability on the participation in international trade - Sèna Kimm Gnangnon (Journal of Risk and Financial Management, 2022)
This paper investigates the effect of countries' structural economic vulnerability (EVI) on their participation in international trade using an unbalanced panel dataset of 118 countries from 1996 to 2018 and the two-step system generalized method of moments estimator. It has revealed several findings. Higher EVI leads to lower participation in international trade, and this negative effect is more pronounced in countries that face higher trade costs. This is particularly the case for landlocked developing countries and the least developed countries. Development aid contributes to dampening the negative effect of EVI on countries' participation in international trade. Moreover, this negative impact may turn out to be positive for high amounts of development aid. The policy implications of this analysis have been discussed.
Keywords: 650; development aid; participation in international trade; structural economic vulnerability; trade costs